Efektivitas Pelatihan Manajemen Waktu untuk Meningkatkan Kemampuan Mengatur Waktu Belajar Siswa SMP - L. M. Sena; Tatik Meiyuntariningsih (Indonesian Journal Publisher, 2025)
This study aims to analyze the effectiveness of time management training in improving learning time management skills among junior high school students who experience difficulties in organizing academic activities. The study employed a mixed quantitative and qualitative approach using a single-case experimental design, involving a seventh-grade student who demonstrated ineffective time use patterns, characterized by irregular study schedules, fatigue, and decreased concentration. Data were collected through the Time Management Assessment for Middle-School Students questionnaire, observations, interviews, psychological tests, and self-recording. Quantitative data were analyzed by comparing pre-test and post-test scores, while qualitative data were analyzed descriptively to illustrate behavioral changes during and after the intervention. The intervention consisted of time management training through the introduction of the Eisenhower Matrix, time blocking, to-do list development, and the use of activity reminder applications. The results showed an improvement in time management scores from the low category (43) to the moderate category (58) after the intervention. In addition to score improvement, observations and student reflections indicated positive changes in scheduling regularity, consistency in recording assignment deadlines, and a better balance between study and rest time. These findings indicate that time management training is effective in enhancing junior high school students’ learning time management skills both quantitatively and qualitatively, and has the potential to support improvements in learning quality and students’ academic well-being.